PERAN PENGELOMPOKAN MOLEKUL PADA HYDROUS ETANOL TERHADAP KINERJA MESIN - I Made Suarta; I Putu Gede Sopan Rahtika; Putu Wijaya Sunu; Ketut Bangse; I Nengah (JURNAL INTEGRASI, 2019)
In this study observed the role of molecular clustering on engine performance produced by hydrous ethanol fuel (95.5% v). The test was performed using variation load for four-cylinder motor. Engine performance is measured using Brake Power Engine load cell type indicator TD 800PM. The engine performance produced by anhydrous ethanol was also tested. The resulting engine performance of both fuels is compared. The results showed that the power produced by hydrous ethanol was slightly higher than that of anhydrous ethanol. The charging effisiency generated by hydrous ethanol is upper than that of anhydrous ethanol.